Diagnóstico técnico de propriedades produtoras de citros nas mesorregiões norte central e noroeste do Paraná - Coelho Júnior, Alberto Ceccon (2016)
The research presents a diagnosis of pests and diseases in Messoregiões North Central and Northwest Paraná. Therefore, we conducted questionnaires applications in 12 properties located in the cities of Santa Monica, Gaucha City, Santa Izabel do Ivai, Apucarana, Arapongas, Parana, Rolândia and Paranavaí. The questionnaires focused questions on owner education, total area of the property, citrus plant area, other sources of income, citrus varieties, marketing, phytosanitary certification of origin, homemade orchard periodic fertilization, surveys for control of diseases, monitoramente of minadoura larva, windbreaks, symptoms and training of citrus canker and the HLB / HLB, preventive control of diseases, control of entry of vehicles and persons in the orchard, decontamination of vehicles, clothing, shoes and hands of workers, use of own material harvesting, knowledge and control of leprosy mite, rust mite and fruit fly, interleaved culture management, use of mowing, legal reserve, use of herbicide, miticide, fungicide, insecticide and use of organic products, perception among pests and fertilization, between nutrition and pests, among management culture and pests, including pests and pesticides, between monoculture and pests and perception of various problems between diseases and pests, resistance to pests and diseases to pesticides, property near the urban area, program environmental regularization of degraded areas program, registered legal reserves, environmental inflation, forest reserve quota, native vegetation, term of conduct approved regarding the regularization of AAP, legal reserve or restricted use, native vegetation in excess of the minimum required amount of legal reserve, rural environmental registry and what are the biggest problems for citrus production. The results raised is possible to conclude that the management conditions of culture held by growers of selected properties are different for each municipality. The citrus industry is very vulnerable in the technical, economic and social, the occurrence of outbreaks of pests and diseases, and rootstock and temporal and spatial continuity of the orchards.